Kepadatan Populasi dan Distribusi Kadal (Mabuya multifasciata. Kuhl) Di Pulau-pulau Kecil Kota Padang - Reszi Juniarmi; Jabang Nurdin; Indra Junaidi Zakaria (Jurnal Biologi Universitas Andalas, 2014)
The study of population density and distribution of Lizard (Mabuya multifasciata. Kuhl) have been carried from June to December 2012 at the Pasumpahan and Sirandah Islands. The survey method and purposive sampling were used in the research, and for direct collecting samples was used visual ecounter survey. Nine individual of M. multifasciata were observed in Sirandah Island with estimate density was 45 ind/ha. The lizard were dispersed through the island of sirandah but was absent in Pasumpahan Island. Keyword: M. Multifasciata, density, distribution, Sirandah, Pasumpahan.